국가영어능력평가시험(NEAT)과 연계한 영어 쓰기 수업모형 개발 - 배주경, 송민영 (교과교육학연구, 2013)
본 연구의 목적은 학교 교육을 통해 학생들의 영어 쓰기 능력을 향상시키고 쓰기 지도 경험이 부족한 교사도 쉽고 효과적으로 쓰기 지도를 할 수 있는 쓰기 수업모형을 개발하는 것이다. 이를 위해 국가 교육과정에서 제시하고 있는 성취기준을 바탕으로 하는 국가영어능력평가시험(NEAT) 2, 3급 쓰기 영역과 연계하여 정규 수업 시간에 교과서를 지도하면서 영어 쓰기 지도를 할 수 있도록 NEAT 쓰기 문항 유형별로 쓰기 수업모형을 개발하였다. 우선 NEAT 쓰기 문항 유형별로 주요 특징과 수업에서 지도할 때 유의점을 분석하였고, 이를 바탕으로 NEAT 쓰기 문항 유형별로 8개씩, 총 48개의 수업지도안을 개발하였다. 개발한 수업지도안은 일반계 고등학교 학생을 대상으로 실제 수업에 적용하여 현장에서의 적용 가능성 여부를 점검하고 교사 및 학생의 의견을 반영하여 수업지도안을 수정하여 완성하였다. 이렇게 완성된 48개의 수업지도안을 쓰기 전 활동, 쓰기 활동, 쓰기 후 활동 등 3단계로 나누어 주요 특징을 분석하여 일상생활에 관한 글쓰기, 자기 의견 쓰기, 상황에 맞는 짧은 글쓰기, 그림의 세부 묘사 완성하기, 편지 쓰기, 그림 묘사하기 및 추론하여 글쓰기 등 6개 쓰기 문항유형별로 하나의 수업모형을 도출하였다. 각 모형별로 수업 목표와 주요 학습 활동을 먼저 간략하게 제시하였고, 쓰기 전 활동, 쓰기 활동, 쓰기 후 활동 등 3단계로 구성하였으며, 우리나라 고등학교 영어 수업에 적용하기 적합하도록 소집단 협동학습과 과정 중심 쓰기 지도 방법을 적용하였다. 무엇보다도 각 단계는 문항 유형에 따라 10분∼20분 정도씩 배정하여 고등학교의 1차시 수업 이내에 적용할 수 있도록 하였다. This study aims to develop instructional models of teaching English writing in order to help high school English teachers teach English writing more easily and effectively in their regular class. To develop the instructional models, this study linked to the writing section of the National English Ability Test (NEAT), which is based on the national curriculum achievement standards. The developmental process was as follows: First, six test items of the writing section of the NEAT were analyzed. Second, a prototype of lesson plan was developed by a specialist of teaching English writing. Third, lesson plans for teaching writing tailored to each writing test item of the NEAT were developed by six experienced high school English teachers. Fourth, the lesson plans were implemented in high school classrooms from various parts of the country in order to gauge the suitability of the lesson plans and to gather feedback from teachers and students. Finally, the lesson plans were analyzed and six instructional models of teaching writing were developed. The study introduced the six models of teaching writing and suggested ways of providing practical help to high school English teachers with limited experience in teaching writing. KCI Citation Count: 3